Interaction mechanism of plant-based nanoarchitectured materials with digestive enzymes of termites as target for pest control: Evidence from molecular docking simulation and in vitro studies - Mishra, Sandhya; Wang, Wenting; de Oliveira, Ivan Pires; Atapattu, Anjana J.; Xia, Shang-Wen; Grillo, Renato [UNESP]; Lescano, Caroline Honaiser; Yang, Xiaodong (Elsevier, 2021)
The integration of nanotechnology for efficient pest management is gaining momentum to overcome the challenges and drawbacks of traditional approaches. However, studies pertaining to termite pest control using biosynthesized nanoparticles are seldom. The present study aims to highlight the following key points: a) green synthesis of AgNPs using Glochidion eriocarpum and their activity against wood-feeding termites, b) testing the hypothesis that AgNPs diminish digestive enzymes in termite gut through in silico analysis. The green synthesis route generated spherical PsAgNPs in the size range of 4-44.5 nm exhibiting higher thermal stability with minimal weight loss at 700 °C. The choice and no-choice bioassays confirmed strong repellent (80.97%) and antifeedant activity of PsAgNPs. Moreover, PsAgNPs exposure caused visible morphological changes in termites. Molecular docking simulation indicated possible attenuation of endoglucanase and bacteria-origin xylanase, digestive enzymes from termite gut, through partial blocking of the catalytic site by AgNPs. Altogether, our preliminary study suggests promising potentials of PsAgNPs for pest management in forestry and agriculture sectors to prevent damages to living trees, wood, crops, etc. As sustainable pest management practices demand low risk to the environment and biodiversity therefore, we recommend that more extensive studies should be performed to elucidate the environmental compatibility of PsAgNPs.
Keywords: AgNPs; Endoglucanase; Molecular docking; Termite control; Xylanase